2012
DOI: 10.4132/koreanjpathol.2012.46.3.233
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Decoy Cell Grading and Its Clinical Implications

Abstract: BackgroundExamination of urine for decoy cells (DCs) is a useful screening test for polyomavirus (PV) activation. We explored the significance of the amount of DCs in persistent shedding, PV nephropathy and acute rejection.MethodsA case-controlled study was performed in 88 renal allograft patients who had DCs detected at least once in four or more urine samples.ResultsFifty one patients were classified into the high-grade shedding group (HG) and 37 patients into the low-grade shedding group (LG) according to D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…The correlation between decoy cell number and the severity of renal injury remains controversial. Koh et al reported that urinary decoy cell number is associated with sustained cell shedding, positive urinary PCR results, and the development of BKVAN [ 66 ]. On the other hand, Singh et al found no correlation between the severity of BKVAN and either decoy cell counts or BKV DNA levels in plasma or urine [ 67 ].…”
Section: Screeningmentioning
confidence: 99%
“…The correlation between decoy cell number and the severity of renal injury remains controversial. Koh et al reported that urinary decoy cell number is associated with sustained cell shedding, positive urinary PCR results, and the development of BKVAN [ 66 ]. On the other hand, Singh et al found no correlation between the severity of BKVAN and either decoy cell counts or BKV DNA levels in plasma or urine [ 67 ].…”
Section: Screeningmentioning
confidence: 99%
“…Figure 2C (g-i) show the underlying urothelium, and the appearance of different parts of the epithelium indicates lesions in the corresponding parts. Figure 2C (j-l) show a decoy cell, which is a shed renal tubular epithelial cell containing polyoma viral inclusion bodies, which are related to BKV (BK virus) infection and renal insufficiency after renal transplantation ( 24 - 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…Routine screening for BK has been shown to be effective in preventing allograft loss in patients with BK viruria or viremia. Reduction of immunosuppression remains the mainstay of BK nephropathy treatment and is the best studied intervention (7). The present study was conducted on thirty-three patients (22 males and 11 females) who received kidney transplantation from living donors.…”
Section: Discussionmentioning
confidence: 99%